Does environmental underperformance duration affect firms' green innovation? Evidence from China. Issue 3 (17th April 2022) - Xue, Shan; Zhang, Lin; Chen, Honghui; Yin, Juelin
Abstract: Does the length of a firm's environmental underperformance shape its green innovation? Drawing on the behavioral theory of the firm, we argue that the duration of a firm's environmental underperformance plays an important role in shaping its green innovation activities. Using the data from Chinese publicly listed firms spanning from 2010 to 2018, we find that the duration of environmental underperformance has a U‐shaped effect on a firm's green innovation, possibly due to competing short‐ and long‐term solutions to regain legitimacy. We also find that this relationship is moderated by environmental underperformance intensity and analyst recommendation pressure. Our study contributes to the literature on green innovation and the behavioral theory of the firm. We discuss the implications for policymakers and managers.